Legal Perspective of Investment Risk Mitigation on Peer-to-peer Lending Platforms - Sahid, Rusdiyanto Rohman; Hardyansah, Rommy; Darmawan, Didit; Negara, Dharma Setiawan; Khayru, Rafadi Khan (Journal of Social Science Studies, 2023)
The introduction of Peer-to-peer Lending (P2PL) platforms have brought significant impact to the financial industry, offering lucrative investment opportunities but also posing various risks. One of the main challenges is the legal protection for investors who invest through these platforms. This study aims to examine the implementation of risk mitigation in P2PL investments in Indonesia through existing regulations, and how these regulations provide effective protection for investors. Using a normative juridical approach, this study identifies various legal provisions implemented by the Financial Services Authority (OJK), such as POJK Number 77/POJK.01/2016, which regulates information technology-based money lending services. The findings of this study show that while regulations have governed various aspects of P2PL operations, implementation challenges remain, particularly with regard to platform compliance and transparency. Stricter oversight and increased education for the society are needed so that investments in these platforms can take place safely and reliably. This study concludes that strengthening regulation and oversight are key to protecting investors and maintaining the sustainability and stability of the P2PL market in Indonesia.